Risk of probable posttraumatic stress disorder in patients with trigeminal neuralgia. Issue 4 (21st April 2019) - Jiang, Che
ABSTRACT: The object of this study was to reveal the occurrence, risk factors and prognosis of posttraumatic stress disorder (PTSD) in patients with trigeminal neuralgia (TN). Adult patients who were diagnosed with TN were prospectively collected from our neuroscience center. Among the 103 patients recruited, thirty (29.1%) participants were identified as probable PTSD cases measured with PTSD Checklist for DSM-5 (PCL-5). Compared with patients without PTSD, patients with probable PTSD were more likely to be female, have severe pain intensity, be with severely interfered general activities, be with more intense depression and anxiety, and be more habitually using maladaptive coping strategies. Logistic regression analysis showed female sex, severe pain intensity, anxiety and depression predicted probable PTSD. In the 28 patients who were initially identified as probable PTSD and had 6-month follow-up data, 21 reported complete pain relief and 4 reported partial pain relief. Fifteen of the patients who experienced complete pain relief recovered from probable PTSD. Our work indicated that PTSD can develop among patients with TN. Complete pain relief through surgical treatments can help most patients with probable PTSD recover, however, psychological support is advised for those who are still obsessed by mental disorders even after pain relief.